Grasshoppers, Crickets and Katydids (Insecta: Orthoptera) of Cuba: an annotated checklist - Yong, Sheyla; Perez-Gelabert, Daniel E. (Zootaxa, 2014)
An annotated list of the Cuban fauna of Orthoptera is presented. For each species we include details of valid names, synonyms, type specimens (type category, sex, locality and depository), geographic distribution and bibliographic references. Clarifying notes are added, as well as comments on the species considered doubtful. A total of 140 species included in 62 genera, 31 subfamilies and 12 families make up the known Cuban fauna of Orthoptera. The family Episactidae, the acridid subfamily Ommatolampidinae with 3 unknown genera, 3 unknown genera of Tettigoniidae (Conocephalinae) and 1 undescribed new genus of Tetrigidae (Cladonotinae) are here recorded for the first time from Cuba. Syntypes are designated for Hygronemobius histrionicus Zayas.